ONLINE GAME BASED ON SERVER-AUTHORITATIVE ARCHITECTURE - Chykrii, Andrii (Sworld-Us Conference proceedings, 2023)
The purpose of developing an online game based on Server-Authoritative architecture is to improve the quality of the game process and reduce the vulnerability to the possibility of game cheating. The following were used to implement the system: Unity Eng